Mapping publications on value creation in construction project settings: a mixed bibliographic and bibliometric analysis - Wang, Ting; Tian, Zidan; Liu, Yan; Wu, Tianyan; He, Qinghua (Journal of Civil Engineering and Management, 2025)
The worldwide interest on value creation has triggered an increasing number of articles, especially after a new paradigm named service-dominant logic was announced in 2004. However, limited research exists on the whole picture of value creation in the field of construction projects. Therefore, the current study is expected to reveal the status and future directions of value creation studies under construction projects. A number of 63 journal articles between 2004 and 2022 were analysed via a combined bibliographic and bibliometric approach, which covers annual publication, institutional and regional contribution, author contribution and keyword analyses. Results indicated that most published articles were based on the developed economies, such as the United Kingdom, Finland and Norway. Keywords such as megaproject, governance, social value and co-creation are emphasised, as analysed using CiteSpace software. Three implications, namely, value creation in developing areas, megaproject value creation, and perceived value perspective, are highlighted. The better understanding of the relevant literature could largely benefit academic peer researchers on value creation. Moreover, the holistic review of the literature body efficiently identifies the knowledge gaps and outlines avenues for following scholars and facilitating high-quality development of the construction engineering industry.